Investigation of Solution Behaviour of Potassium Halides in Aqueous Solution of L- Proline at Different Temperatures: A Physicochemical Approach - Sikdar , Partha Sarathi; De , Pritam; Alam , Firoj; Ghosh , Biswajit; Ali , Salim; Hossain , Ayesha; Sharma, Antara; Bomzan , Pranish; Mallick , Kangkan; Roy , Mahendra Nath (Progress in Chemical Science Research Vol. 5, 2022)
An analysis on the molecular interactions of potassium halides in aqueous mixture of L-Proline have been studied by measuring density (\(\rho\)) and viscosity (\(\eta\)) at three different temperatures (298.15, 308.15 and 318.15 K). Apparent molar volume (\(\phi\)v ) and viscosity B-coefficients were derived using Masson equation and Jones-Dole equation respectively and these derived parameters interprets the existing ion-solvent and ion-ion interactions in solution. The structure-making or breaking capacity of the electrolyte under investigation has been discussed in terms of sign of (\(\varphi\)V0 /\(\delta\)T)p.